MPNP, UMP organise Discourse on Harmony Workers, Sustainable Economy - Muhammad Ashraf, Fauzi (UMPSA, 2023)
KUANTAN, 6 July 2023 - The Pahang State Employees Council (MPNP) in collaboration with Universiti Malaysia Pahang (UMP) successfully attracted more than 100 entries consisting of departments, agencies, non-governmental organisations (NGOs), higher education institutions (IPTs) and industry players in Pahang Darul Makmur in organising the Discourse of Harmony Workers, Sustainable Economy programme.